Rising Trends of Cesarean Section in Bangladesh: Associated Factors and Long-Term Complications on Health of Mother and Children - Hossain, Md. Altaf; Jahan, Ishrat; Haque, Mohammad Mozibul; Sarwar, Nazmul; Yeasmin, Nilufa; Islam, Dilshad (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: With taking into consideration of the high cesarean section (CS) rate, the objectives of this study were to ascertain factors associated with and point out metamorphose complications with high CS rates in Bangladesh. Subjects and Method: A cross-sectional study accounted for data collection from rural (196) and urban (241) women who gave birth to babies between 2005 and 2018 in Chattogram, Bangladesh. The study subjects were selected by using a systematic random sampling technique and the sample size was determined by using web-based Raosoft software. The delivery modes were dependent variables whereas influential factors and complications related to delivery were independent variables. The data were collected through face-to-face interviews using a pre-structured questionnaire. The height and weight of the participants were measured by using a stadiometer and weighing machine respectively. Data analysis was done by using regression analysis. Results: The results divulged that mingling of relative influence and doctor’s profit-making tendency, obstetric factors, and demand from a family with higher socioeconomic status contributed to the recent increased cesarean rate in urban areas (41.5%). The distended abdomen in mothers (OR= 5.11, 95% CI= 2.98 to 8.76) was strongly associated with CS (p< 0.05), and back pain, and urinary incontinence were about one and half times higher in CS mothers. However, miscarriage and pelvic organ prolapse were associated with decreased risks of CS. Postnatal complications include cold fever (OR= 11.95, 95% CI= 7.02 to 20.35), and pneumonia (OR= 5.79; 95% CI= 2.71 to 12.36) were highly prevalent in children with cesarean delivery. Conclusion: Cesarean section has become alarmingly increased in urban rather than rural areas of Bangladesh in recent decays. Awareness-raising, doctor commitment, government policy, and strict monitoring of private health facilities are needed to control high rates of cesarean delivery. Keywords: cesarean delivery; vaginal delivery; demographic factors; obstetric factors; postpartum complications. Correspondence: Md. Altaf Hossain, Department of Animal Resources Science, Sunchon National University, Suncheon, Jeollanam-do, South Korea. Telephone: +8201098532108; Email: altaf@cvasu.ac.bd